Honesty in a Signaling Model of Tax Evasion - Vitaly Pruzhansky (Tinbergen Institute, 2004)
We study the phenomenon of tax evasion using a simple signaling model, in which the signal is taxpayer's reported income. The novelty of our approach lies in the way we define honesty. Specifically, we advocate the view that there are no absolutely honest taxpayers: all taxpayers may under certain conditions become evaders. We investigate the implications of this type of honesty on the equilibria of the model, and compare it to the basic case, in which honesty is absent. Our analysis completely characterizes all perfect Bayesian Nash equilibria of the game, assesses their stability and welfare properties.
Keywords: C72; H26; 330; Auditing; equilibrium refinements; tax morale; underground economies; Steuerstrafrecht; Signalling; Spieltheorie; Theorie